2020
DOI: 10.2147/ott.s261973
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA CDKN2B-AS1 Facilitates Lung Cancer Development Through Regulating miR-378b/NR2C2</p>

Abstract: Aim: Long noncoding RNA (lncRNA) have proved to be important regulators in various diseases. CDKN2B-AS1 was a newly identified tumor-related lncRNA, and previous studies have reported its function in laryngeal squamous cancer and osteosarcoma. However, the function and mechanism of lncRNA CDKN2B-AS1 in lung cancer are still unknown. Methods: Cell proliferation, invasion, migration and apoptosis were detected via CCK-8, transwell assay and Western blot. Bioinformatics analysis was used to predict the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Based on our data, lncRNA CDKN2B-AS1 played an oncogenic factor in breast cancer. It is consistent with the previous other studies about its role in most cancers, which indicated that CDKN2B-AS1 exerted a pro-cancer effect [ 40–42 ]. For examples, in renal clear cell carcinoma, lncRNA CDKN2B-AS1 affected the malignancy through epigenetically activating NUF2 (NUF2 Component of NDC80 Kinetochore Complex) transcription [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Based on our data, lncRNA CDKN2B-AS1 played an oncogenic factor in breast cancer. It is consistent with the previous other studies about its role in most cancers, which indicated that CDKN2B-AS1 exerted a pro-cancer effect [ 40–42 ]. For examples, in renal clear cell carcinoma, lncRNA CDKN2B-AS1 affected the malignancy through epigenetically activating NUF2 (NUF2 Component of NDC80 Kinetochore Complex) transcription [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…In renal clear cell carcinoma, CDKN2B-AS1 exerts its carcinogenic activity by recruiting CREB-binding protein and three epigenetic modification complexes containing SET and MYND domains to the promoter region of the Ndc80 mitochondrial complex (NUF2) ( Xie et al, 2021 ). In lung cancer, CDKN2B-AS1 acts as a cavernous body by adsorbing miR-378b and regulating miR-378b/NR2C2 to promote cancer development ( Wang et al, 2020 ). However, the expression and role of CDKN2B-AS1 in EC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-378b has been reported to modulate cancer progression as a tumor suppressor. It has been reported that long Noncoding RNA CDKN2B-AS1 contributes to development of lung cancer by modulating miR-378b/NR2C2 axis [ 31 ]. Meanwhile, SLC2A1 plays an essential function in the regulation of glycolysis and progression of glioma.…”
Section: Discussionmentioning
confidence: 99%